Synthesis, structure and magnetic properties of CoFe2O4 ferrite nanoparticles. (4th May 2018) - Su, K P; Zhao, C Y; Wang, H O; Huang, S; Liu, Z W; Huo, D X
Abstract: CoFe2 O4 nanoparticles with different morphologies were successfully synthesized by co-precipitation method, followed by heat treatment. XRD patterns showed that a single phase ferrite was obtained. By the method of heating, the effect on the morphology and properties of the CoFe2 O4 nanoparticles is studied. The synthesis conditions (oxidation process and temperature) dominated the formation of crystals with different morphologies. The oxidation and growth mechanisms behind the formation of CoFe2 O4 nanocrystals were investigated. The saturation magnetization of the CoFe2 O4 samples was lower than the bulk value, which could be explained by the reduction of the particle size. The highest value of coercivity of all the samples is 155.5 kA m −1 for the CoFe2 O4 nanorods. Compared with the H c value of cobalt ferrite nanoflakes, the rod shaped cobalt ferrite has a higher coercivity. The remanence ratio of the CoFe2 O4 /FeCo is 0.56, which indicates a strong exchange coupling between hard and soft phase.